Student Anxiety In Online Learning During The Covid-19 Pandemic - Putri, Fiona Adipa; Yarni, Linda; Rahmi, Alfi; Santosa, Budi (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2024)
This research is motivated by the things that students feel in online learning during the pandemic (Covid-19) such as nervousness, excessive sweating, sweaty palms, dry mouth, frequent nightmares, palpitations, difficulty concentrating, feeling anxious, feeling inadequate, restless, having trouble sleeping at night, irritability, which are some of the things that happen when someone experiences anxiety. The purpose of this study was to determine the anxiety felt by third semester students of the Guidance and Counseling Study Program, Faculty of Tarbiyah and Teacher Training, UIN Sjech M. DjamilDjambekBukittinggi while doing online learning during the pandemic (Covid-19). This study used field research in a qualitative descriptive form, the key informants were third semester counseling guidance students and the supporting informants were the students' parents. The data collection technique used was interview using snowball sampling. Data processing using the method of data reduction, data presentation, and data verification. Based on the results of the study, it can be concluded that the student anxiety in online learning during the pandemic (Covid-19) at UIN Sjech M Djamil Djambek Bukittinggi are from the family environment, from the social environment, difficult internet networks, studying while working, limited learning media, inability to complate assignments and limited access and resources.